Literasi Informasi Kesehatan Nifas Ibu Hamil Berstatus Sosial Menengah ke Bawah - Tito Yustiawan; Nurhasmadiar Nandini (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
Background: Post-partum health information is hardly accessible to pregnant women. In fact, post-partum health literacy for pregnant mothers in relation to socio-economic factors allows the decline of post-partum morbidities.Aim: This research aimed to analyse the post-partum health information literacy of pregnant women with middlelow social status.Method: This was a quantitative study by using a direct survey technique to assess respondents’ information literacy about post-partum health. There were 79 pregnant women to take part in this study. They only completed their high school degree as their highest educational level, and their family income was less than Rp 2,000,000($180) per month. This indicated that these participants are coming from middle-low social status. A selfdeveloped questionnaire was used in this study to be filled by respondents.Results: Results showed that nearly half of respondents (44.1%) found post-partum health information for their self-hygiene well-being after baby delivery process finished. Information accessed by pregnant women were elaborated from other people (66.1%) like as parents, relatives, colleagues, or health officers. Most of the participants agreed to trust captured information (78%), but there were only little use the information (11.9%).Conclusion: To summarize, the health information literacy of pregnant mothers with middle-low status was tenuously elaborated from other people, and most of them believed it. It is possible that information obtained from other people is incorrect, so pregnant mothers might use wrong information.Keywords: health, information literacy, post-partum, pregnant women